2017
DOI: 10.1111/hae.13206
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of plasminogen activator inhibitor‐1 and bleeding phenotype in patients with von Willebrand disease

Abstract: In young female VWD patients, we observed that low PAI-1 levels were associated with a higher bleeding score, which may partly explain the observed variability in bleeding phenotype in VWD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this substudy, we used different classification criteria than in previous projects in the WiN study. While using the most contemporary criteria makes for a better extrapolation of our data, caution should be used when comparing our results with previous reports from the WiN study, especially those on the association between fibrinolysis and bleeding 27,28 . We have previously shown that the requirement of VWF propeptide levels <5 U/dL in addition to low VWF antigen and activity levels improves the classification of type 3 VWD 11 …”
Section: Discussionmentioning
confidence: 62%
“…In this substudy, we used different classification criteria than in previous projects in the WiN study. While using the most contemporary criteria makes for a better extrapolation of our data, caution should be used when comparing our results with previous reports from the WiN study, especially those on the association between fibrinolysis and bleeding 27,28 . We have previously shown that the requirement of VWF propeptide levels <5 U/dL in addition to low VWF antigen and activity levels improves the classification of type 3 VWD 11 …”
Section: Discussionmentioning
confidence: 62%
“…In addition, the potential role for variation in hemostatic pathways intertwined with thrombin generation, such as fibrinolysis, to nudge hemostasis either toward or away from balance, is increasingly apparent. Age to begin prophylactic factor replacement 22,24 Differences in severity between HA and HB 25,26 Null versus non-null mutation 11,32,34 Co-inheritance of a prothrombotic mutation 8,[39][40][41][42][43] Interindividual differences in fibrinolysis 67,73,76 Interindividual differences in cellular function 80,85 Heterogeneity in response to gene therapy 93,95 Abbreviations: HA, hemophilia A; HB, hemophilia B; PWH, people with hemophilia.…”
Section: Resultsmentioning
confidence: 99%
“…The balance between tPA and PAI-1 levels in PWH is not well characterized, but it is conceivable that the regulatory relationship between these two components may become destabilized during a bleeding event. The role of PAI-1 in PWH remains unclear, but it has been shown in VWD that low levels of PAI-1 are associated with an increase in severity of clinical bleeding phenotype 67 and it remains to be determined whether this is also the case in PWH. α 2 -AP deficiency results in accelerated fibrinolysis and excessive bleeding 68 ; however, whether α 2 -AP levels vary between individual PWH has yet to be fully investigated.…”
Section: Interindividual Differences In Fibrinolytic Activity As a Pomentioning
confidence: 99%
“…This suggests that the severe bleeding problems of FXIII-deficient patients are not primarily caused by enhanced clot lysis, but by impaired (physical) stability of the clots due to insufficient formation of γ chain dimers and possibly α chain polymers. Enhanced fibrinolysis could contribute, however, to the severity of the bleeding tendency, as recently observed in a subpopulation of patients with von Willebrand disease [54]. …”
Section: (Patho)physiologic Aspectsmentioning
confidence: 99%